Carboxylated Adsorbent from Confiscated Cigarette Tobacco for Methylene Blue Removal - Saad, Saiful Azhar; Md. Isa, Khairuddin; Bose Gopinath, Subash Candra; Kasim, Farizul Hafiz; Ibrahim, Naimah; Abd Aziz, Mohd Aizudin (International Journal of Integrated Engineering, 2026)
The widespread use of synthetic dyes in various industries has led to severe water pollution due to their toxic, mutagenic, and carcinogenic properties. This study investigates the potential application of an adsorbent prepared from confiscated cigarette tobacco for methylene blue (MB) removal. The adsorption performance of chemically treated confiscated cigarettes (CCC) was compared with untreated confiscated cigarettes (CC) and commercial activated carbon (CAC). The effects of contact time, initial MB concentration, adsorbent dosage, and solution pH on the MB removal efficiency were evaluated. SEM analysis of CCC revealed an increased in pore formation and structural modification, while FTIR confirmed the presence of carboxyl functional groups, indicating successful chemical activation. The optimum conditions for MB removal were 180 minutes of contact time, pH 8, with the adsorption capacity of 8.38 mg/g. Isotherm analysis showed that MB removal followed the Langmuir model (R² = 0.9734), indicating monolayer coverage, while kinetic data fitted the pseudo-second-order model (R² = 0.9861), suggesting chemisorption as the dominant mechanism involving strong adsorbate–adsorbent interactions and improved adsorption stability. CCC exhibited higher adsorption efficiency than CC, although CAC remained superior. This study introduces a novel waste management approach for the increasing quantities of confiscated cigarette waste generated due to stringent anti-smuggling enforcement. Overall, CCC demonstrates promising potential and economic feasibility as an alternative adsorbent, particularly for small-scale wastewater treatment applications.